The impact of uncertainty on credit risk: The case of Vietnam commercial banks - Van, Nguyen Thi; Khanh, Pham Ngoc; Quang, Bui Van (International Journal of Innovative Research and Scientific Studies, 2025)
The increasing trend of credit risk in the Vietnamese commercial banking system has recently been the focus of many domestic economic forums and conferences. The purpose of this study is to analyze the impact of uncertainty regarding total bank assets and other factors causing credit risk in Vietnamese commercial banks. The paper employs the two-step SGMM estimation method and a sample of 30 Vietnamese commercial banks during the period 2006–2021. The research results indicate that uncertainty about total assets causes bank credit risk. In addition, factors such as bank size, economic growth (GDP), and inflation also affect bank credit risk. Meanwhile, our research results do not find evidence that credit growth and credit risk have a supporting correlation. These findings provide bank managers with a better understanding of total asset uncertainty, which serves as a basis for management efforts to enhance credit risk management.